Body mass index and risk of Parkinson, Alzheimer, Dementia, and Dementia mortality: a systematic review and dose–response meta-analysis of cohort studies among 5 million participants. (4th March 2022) - Rahmani, Jamal; Roudsari, Arezoo Haghighian; Bawadi, Hiba; Clark, Cain; Ryan, Paul M.; Salehisahlabadi, Ammar; Rahimi sakak, Fatemeh; Goodarzi, Naser; Razaz, Jalaledin Mirzay
ABSTRACT: Objective: Inconsistent results regarding the association between the Body Mass Index (BMI) and brain disorders have been reported. We performed this study to investigate the association between BMI and risk of Parkinson, Alzheimer, Dementia and Dementia-mortality. Methods: A systematic search was conducted up to April 2019 in MEDLINE/PubMed, SCOPUS, and Cochrane Library. Results pooled with random-effects model. Results: Totally, 29 articles which were included in this study with4, 978, 621 participants. The pooled HR for Parkinson's in the underweight person was 1.20 (95%CI1.10–1.30). The pooled HR for dementia in underweight and overweight category was 1.23 (95%CI = 1.05–1.45) and 0.88 (95%CI = 0.83–0.94), respectively. There is not any significant relation between each categories of BMI and Alzheimer disease. The pooled HR for dementia in underweight and overweight category was 1.36 (95%CI = 1.14–1.63) and 0.81 (95%CI = 0.49–1.33), respectively. The non-linear association between BMI and risk of Dementia-mortality was significant ( p = 0.001, Coeff = 0.003). Conclusion: This study highlights underweight related to increase incidence of Parkinson, Dementia, and Dementia mortality but no on Alzheimer disease.